2018
DOI: 10.1186/s13063-018-2676-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative patient education on the prevention of postoperative complications after major visceral surgery: the cluster randomized controlled PEDUCAT trial

Abstract: BackgroundThe prevention of postoperative complications is of prime importance after complex elective abdominal operations. Preoperative patient education may prevent postoperative complications and improve patients’ wellbeing, but evidence for its efficacy is poor. The aims of the PEDUCAT trial were (a) to assess the impact of preoperative patient education on postoperative complications and patient-reported outcomes in patients scheduled for elective complex visceral surgery and (b) to evaluate the feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…A more recent RCT of 73 patients with colorectal cancer, reported improved body image after surgery and enhanced recovery of self-reported global health status and reduced LOS after extra preoperative group education [ 18 ]. However, meta-analyses on education for patients undergoing elective spinal surgery as well as a cluster RCT in patients undergoing visceral surgery did not report any sustained benefit on the majority of clinical outcome [ 19 , 20 ]. The educational intervention proves hard to standardize, and there is a paucity in research assessing its benefits for bariatric surgery.…”
Section: Results: Evidence Base and Recommendationsmentioning
confidence: 99%
“…A more recent RCT of 73 patients with colorectal cancer, reported improved body image after surgery and enhanced recovery of self-reported global health status and reduced LOS after extra preoperative group education [ 18 ]. However, meta-analyses on education for patients undergoing elective spinal surgery as well as a cluster RCT in patients undergoing visceral surgery did not report any sustained benefit on the majority of clinical outcome [ 19 , 20 ]. The educational intervention proves hard to standardize, and there is a paucity in research assessing its benefits for bariatric surgery.…”
Section: Results: Evidence Base and Recommendationsmentioning
confidence: 99%
“…The clinician and researcher developed questionnaire has been in use since 2017 (Additional file 2 ) and consists of five core and three follow up questions. Participants completed three items on a five point likert scale (ranging from strongly disagree to strongly agree) aimed at assessing patient satisfaction and based on statements previously used to evaluate pre-operative education [ 33 ]. Additional questions provided further demographic data including highest level of education and history of smoking.…”
Section: Methodsmentioning
confidence: 99%
“…A clinical trial in Taiwan also reported no effect of the treatment when the outcome was current level of pain and the average level of pain, instead of worst pain intensity [52]. It is also worthy to mention that a recent RCT from Germany, reported no superiority of preoperative patient education over the standard of care for most of the outcome measures authors used, including postoperative pain intensity [53]. Patients' participation in decision making was notably higher in the treatment group compared to the control at 24 hours after the surgery.…”
Section: Discussionmentioning
confidence: 99%